2017
DOI: 10.4236/health.2017.95061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methionine on the Immune Function in Animals

Abstract: Nutrition and immunity are the hot topics in animal's production, and the effects of methionine on the immunity are already confirmed as the deep research on the nutrition of amino acid and immune function. However, the relationship of the methionine and immunity has not been elucidated clearly, this review aims to clarify the effects of methionine on immune function in the aspects of growth and development immune organs, the histological structure of the immune organs, non-specific immunity, humoral immunity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…Methionine is a sulfuric amino acid that is important in protein synthesis. Some suggested that methionine can act as an immune regulatory factor, like IL-1 or insulin-like growth factor I. Methionine can protect cells from oxidative damage, which can also play a role in preeclampsia [ 21 , 22 , 23 , 24 ]. Methionine is also a precursor of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Methionine is a sulfuric amino acid that is important in protein synthesis. Some suggested that methionine can act as an immune regulatory factor, like IL-1 or insulin-like growth factor I. Methionine can protect cells from oxidative damage, which can also play a role in preeclampsia [ 21 , 22 , 23 , 24 ]. Methionine is also a precursor of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…16 Antioksidan diketahui dapat menurunkan stress oksidatif dimana antioksidan ini memiliki kontribusi dalam menurunkan sitokin-sitokin inflamasi sehingga menyebabkan penurunan pada jumlah leukosit. 17 Asupan lemak yang berlebihan, terutama asupan lemak jenuh yang terjadi pada kelompok nonvegetarian, dapat meningkatkan simpanan lemak di dalam tubuh (trigliserida) sehingga mengakibatkan keseimbangan lemak positif dan peningkatan akumulasi jaringan adiposa. Trigliserida diketahui berhubungan dengan peningkatan jumlah sel darah putih di peredaran darah karena trigliserida memberikan suplai energi bagi pembuatan sel darah putih.…”
Section: Pembahasanunclassified
“…Contrary to the beneficial effects of methionine restriction, other reports also showed that long‐term methionine restriction in young animals alters bone structure, stunts growth, increases homocysteine level, hepatocellular injury, oxidative stress, inflammation, and methionine deficient diet increases the risk of developing nonalcoholic steatohepatitis . Further, methionine is important to the immune system and intake of a methionine‐restricted diet over a long time makes an individual susceptible to chronic infections …”
Section: Introductionmentioning
confidence: 99%
“…[20,[38][39][40][41][42] Further, methionine is important to the immune system and intake of a methionine-restricted diet over a long time makes an individual susceptible to chronic infections. [43,44] In view of variety of literature on l-Met-S in metabolic diseases, current in vivo experiment was designed to study the effect of l-Met-S in HFD + low dose STZ-induced T2DM animals. Further, the study also aims to investigate the changes in OCM and epigenetic changes by l-Met-S in HFD + low dose STZ-induced T2DM animals.…”
Section: Introductionmentioning
confidence: 99%